US aid, US educated leaders and economic ideology - Anna Minasyan (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2016)
The Unites States (US) explicitly promotes its economic ideology of free-markets through its development aid programs. It also sees international education in the US as way of spreading its own ideas and values among the powerful elite in developing countries. US educated aid-recipient country leaders may thus receive more aid from the Unites States, if they share both the cultural values and economic ideology of the US. I test this hypothesis using a panel fixed-effects regression model for 896 leaders and 143 countries over the period from 1981 until 2010 (unbalanced). I address self- and donor-selection biases by including leader dummies in the regression analysis in addition to the country and year fixed effects. In result, I find that the US allocates 30 percent more bilateral aid to US educated right leaders compared to the US educated left leaders. Heterogeneity analysis reveal that this result is driven by right-wing US leaders (Republican), the effect of which is robust to exclusion of Latin American countries and inclusion of lagged effects.
Keywords: 330